Health behaviours and attitudes towards being role models - Blake, Holly; Harrison, Catherine (Mark Allen Healthcare, 2013)
Nurses are often viewed by the general public as role models for health. This study investigated health behaviours in pre-registered nurses and their attitudes towards being role models to their patients. In total, 540 pre-registered nurses self-reported their level of physical activity, smoking habits, alcohol intake and dietary habits. Overall, 24% were overweight or obese, 47% were not physically active enough to benefit their health, 73% did not eat the recommended five portions of fruit and vegetables per day, 40% reported binge drinking and 17% were smokers. However, respondents commonly held the belief that nurses should be role models for health, although opinions varied according to the individual's own health profile. Despite being educated in health promotion practice, health behaviours were less than exemplary in this sample and for many, appeared contradictory to participant's beliefs that nurses should be exemplars for health. Nursing education should emphasise the importance of translating learning to their own health behaviours to support a healthy future NHS workforce.